PENERAPAN KONSELING KELOMPOK ANALISIS TRANSAKSIONAL DALAM DUNIA PENDIDIKAN - Pratiwi, Awalya Siska; Muslihati, Muslihati; Rachmawati, Indriyana (Universitas Muria Kudus, 2022)
The purpose of this paper is to describe the application of transactional analysis group counseling in the world of education. Literature review is the method used in this writing. The implementation of Transactional Analysis counseling has been implemented in schools from the elementary school to the tertiary level. In implementing the Transactional Analysis approach, it can be used for individual counseling, but it is more appropriate if it is carried out in group counseling. The basic concepts of Transactional Analysis include Injunction, Stroke, Life Script, Ego State, Life Position, Games and Redecesions. In Transactional Analysis counseling, individuals are said to be healthy and win when they are in the position of I'm OK, you're OK. There are 3 stages of transactional analysis in group counseling, namely the first is the initial stage, the second is the work stage, and the third is the final stage.